The Etymologies of Perkūnas and aitivaras - Ostrowski, Norbert (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English]The present paper consists of two parts. The first one is dedicated to the etymology of the Lithuanian noun perkūnas (“thunder, thunderbolt”). According to the author, perkūnas is a derivative with a possessive suffix -Hon- / -Hn from the IDE *perkwu-s (“oak”). The second part concerns the origin of the Lithuanian aitvaras (“supernatural being,” OLith. aitvaras). The analyzed noun is an instance of the so-called Caland system in the Baltic languages, and it traces back to the older compound word with the meaning *“being bestowed with flaming power.”